Francis Xavier’s self-perception in a Japanese mirror - Takamura Altuna, Javier (2023)
This paper considers Xavier’s famous statements in his first letter from Japan, and other missives, wherein he states his high views and expectations of the Japanese people. Xavier located the archipelago on a par with Europe with regards to the people and culture, to the extent that back in Europe, Japan could have been considered to be a very similar civilisation. His remark of Japan that it is an island where there were “nor moors neither jews” beforehis arrival, hints a subtle search for the ideal mission field. Especially as he saw in the Japanese people hidalguíaand reason, and consider this new mission an ideal field, almost as utopic to receive the Gospel. His observations of Japan reveal his own self-perceptions and his modelling on the Apostle to the Gentiles.